Sitosterolemia—10 years observation in two sisters - Lara Veit (JIMD Reports, 2019)
Abstract Familial hypercholesterolemia due to heterozygous low‐density lipoprotein‐receptor mutations is a common inborn errors of metabolism. Secondary hypercholesterolemia due to a defect in phytosterol metabolism is far less common and may escape diagnosis during the work‐up of patients with dyslipidemias. Here we report on two sisters with the rare, autosomal recessive condition, sitosterolemia. This disease is caused by mutations in a defective adenosine triphosphate‐binding cassette sterol excretion transporter, leading to highly elevated plant sterol concentrations in tissues and to a wide range of symptoms. After a delayed diagnosis, treatment with a diet low in plant lipids plus ezetimibe to block the absorption of sterols corrected most of the clinical and biochemical signs of the disease. We followed the two patients for over 10 years and report their initial presentation and long‐term response to treatment.